The Effect of Cassava Peel Starch Addition to Bioplastic Biodegradation Based On Chitosan On Soil and River Water Media - Mahfud Syuhada; Sintia Ainus Sofa; Endaruji Sedyadi (Biology, Medicine, & Natural Product Chemistry, 2020)
The study of the relationship between starch addition to biodegradation of bioplastics has been carried out. This study aims to understand the biodegradability of chitosan-based bioplastics with additional cassava peel starch on soil and river water media. This research was conducted through four stages, namely making starch from cassava peel waste, making bioplastics using the blending and castingwet processes method with variations of starch 5, 10, 15 and 20 ml. Testing physical mechanical properties including water resistance, thickness, tensile strength, elongation, and modulus young. Testing the characteristics of bioplastics functional groups was carried out using FTIR (Fourier Transform Infrared) and biodegradation testing of bioplastics carried out on soil and river water media. The results of bioplastics research with variation 5 ml produce good mechanical physical properties. Bioplastics produced water resistance value of 45.03%, thickness of 0.0190 mm, tensile strength of 49.93 MPa, elongation of 3.068% and Young modulus of 1627.63 MPa. Bioplastics biodegradation test was observed by measuring the decrease in sample mass. The biodegradation test results in soil and river water media respectively showed a decrease in bioplastic mass up to 63% and 54%. The biodegradation rate of the calculation results on soil media is −0,1502 and in river water media is −0,0948.